2021
DOI: 10.1021/acs.joc.1c00438
|View full text |Cite
|
Sign up to set email alerts
|

Chromium–Salen Complex/Nitroxyl Radical Cooperative Catalysis: A Combination for Aerobic Intramolecular Dearomative Coupling of Phenols

Abstract: We describe an aerobic intramolecular dearomative coupling reaction of tethered phenols using a catalytic system consisting of a chromium−salen (Cr−salen) complex combined with a nitroxyl radical. This novel catalytic system enables formation of various spirocyclic dienone products including those unable to be accessed by previously reported methods efficiently under mild reaction conditions. Note pubs.acs.org/joc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Our study to develop a catalytic system to promote the precise aerobic oxidation of organic compounds recently revealed that a combination of a chromium–salen complex (Cr–salen) and 2,2,6,6-tetramethylpiperidine N -oxyl (TEMPO) efficiently catalyzed the aerobic intramolecular dearomative coupling of tethered phenols. , We explored the catalytic system and different synchronous systems of Cr–salen with various additives, which alter the reactivity and selectivity of the Cr–salen-catalyzed transformation. Cr–salen catalyzed the dimerization of 3,5-disubstituted hydroxystilbenoids efficiently to form quinone methide dimers or quadrangularin-type cyclized products, depending on the hydroxystilbenoid substituent.…”
mentioning
confidence: 99%
“…Our study to develop a catalytic system to promote the precise aerobic oxidation of organic compounds recently revealed that a combination of a chromium–salen complex (Cr–salen) and 2,2,6,6-tetramethylpiperidine N -oxyl (TEMPO) efficiently catalyzed the aerobic intramolecular dearomative coupling of tethered phenols. , We explored the catalytic system and different synchronous systems of Cr–salen with various additives, which alter the reactivity and selectivity of the Cr–salen-catalyzed transformation. Cr–salen catalyzed the dimerization of 3,5-disubstituted hydroxystilbenoids efficiently to form quinone methide dimers or quadrangularin-type cyclized products, depending on the hydroxystilbenoid substituent.…”
mentioning
confidence: 99%